Unveiling the Vital Role of Long Non-Coding RNAs in Cardiac Oxidative Stress, Cell Death, and Fibrosis in Diabetic Cardiomyopathy - Yuan Tian; Ziting Gao; Wenyun Liu; Jinjie Li; Xin Jiang; Ying Xin (MDPI AG, 2022)
Diabetes mellitus is a burdensome public health problem. Diabetic cardiomyopathy (DCM) is a major cause of mortality and morbidity in diabetes patients. The pathogenesis of DCM is multifactorial and involves metabolic abnormalities, the accumulation of advanced glycation end products, myocardial cell death, oxidative stress, inflammation, microangiopathy, and cardiac fibrosis. Evidence suggests that various types of cardiomyocyte death act simultaneously as terminal pathways in DCM. Long non-coding RNAs (lncRNAs) are a class of RNA transcripts with lengths greater than 200 nucleotides and no apparent coding potential. Emerging studies have shown the critical role of lncRNAs in the pathogenesis of DCM, along with the development of molecular biology technologies. Therefore, we summarize specific lncRNAs that mainly regulate multiple modes of cardiomyopathy death, oxidative stress, and cardiac fibrosis and provide valuable insights into diagnostic and therapeutic biomarkers and strategies for DCM.